2008
DOI: 10.3390/molecules13112908
|View full text |Cite
|
Sign up to set email alerts
|

Cerium (IV) Ammonium Nitrate (CAN) Catalyzed One-pot Synthesis of 2-Arylbenzothiazoles

Abstract: A one-pot synthesis of 2-arylbenzothiazoles from the reaction of 2-amino-thiophenol and aromatic aldehydes catalysed by cerium (IV) ammonium nitrate (CAN) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…We have initiated a program aimed at exploring the potential of CAN in organic transformation. This effort led to the development of a onepot CAN-catalyzed synthesis of 2-arylthiazoloes 116 from the reaction of 2-aminothiophenol 115 and aromatic aldehydes (Scheme 26 and Table 18) [82].…”
Section: Solvent-free Reactionsmentioning
confidence: 99%
“…We have initiated a program aimed at exploring the potential of CAN in organic transformation. This effort led to the development of a onepot CAN-catalyzed synthesis of 2-arylthiazoloes 116 from the reaction of 2-aminothiophenol 115 and aromatic aldehydes (Scheme 26 and Table 18) [82].…”
Section: Solvent-free Reactionsmentioning
confidence: 99%
“…The cyclocondensation of aryl aldehydes and 2-aminothiophenol have been performed by Itoh et al (46) using scandium triflate and obtained better yields of the benzothiazoles. Al-Qalaf et al (47) have reported the cyclization of 2-aminothiophenols and aldehydes using ceric ammonium nitrate as an oxidant in methanol and obtained moderate yields of the benzothiazoles.…”
Section: *Corresponding Author Email: Manera@indiatimescommentioning
confidence: 99%
“…The reaction of equimolar amounts of 1 (2-aminothiophenol) and 2 (aromatic aldehydes) in methanol (MeOH) in the presence of CAN resulted into corresponding 2-arylbenzothiazoles 4 in good yields (75-89%) via the intermediate formation of schiff's bases 3 [44].…”
Section: Reaction Of 2-aminothiophenol and Aromatic Aldehydesmentioning
confidence: 99%